Investment in green economy as a potential source of value added - Jan Klasinc (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose - The hypothesis of the paper is that domestic value added created by exports in Croatia could be increased by investments in green economy. Methodology - In the developed economies only specific products, processes and functions that outperform emerging economies in Global Value Chains are able to profit from the larger share of value added. Large portion of "green economy" is knowledge intensive, and if knowledge based economy (KBC) plays a significant role in determining the domestic value added created by exports, economies with a larger stock of KBC should have a larger difference in VAX between knowledge-intensive industries and less knowledge-intensive industries. Domestic value added embodied in exports can be proxied by attracted FDI. Findings - The results seem to show some support to the hypothesis. In Croatia it has already been shown that sectors of economy with larger stock of intellectual capital measured by Intellectual Capital Efficiency (ICE) index attracted more FDI, which can also serve as a predictor for larger value added in exports due to higher productivity. Knowledge intensity of 18 industries in the US as the benchmark economy shows that "Electrical and optical equipment" has above average knowledge intensity of 0,53, and it can be matched with "green economy" in Croatian industries that attracted more FDI and have higher levels of KBC. Research limitations and implications - Although this study is limited just to KBC, as an extension, the potential role of financial development could be included. Also, the length of time series for VAX measured by OECD does not allow for more thorough analysis. Originality/value - Although not conclusive, this paper is an important first step giving direction to subsequent studies of effects of KBC on value added.
Keywords: F21; D24; 330; value added; global value chains; electronics; green economy; competitiveness